Asymmetry and skin pigmentary anomalies in chromosome mosaicism. Issue 9 (September 1994) - Woods, C G; Bankier, A; Curry, J; Sheffield, L J; Slaney, S F; Smith, K; Voullaire, L; Wellesley, D
Abstract : We report six persons mosaic for a chromosome anomaly. All were mentally retarded and dysmorphic. Unilateral or asymmetrical features were found in all cases, in one an unusual transverse terminal limb anomaly, and in the others various degrees of hemiatrophy of the left side of the body. Five of the subjects had skin pigmentary anomalies which were distributed in the lines of Blaschko. The abnormal cell lines found were ring chromosome 22, trisomy 22, a large acrocentric marker, a deletion of 18q, a deletion of 8q, and triploidy. In four cases the clinical diagnosis was only confirmed by skin biopsy. In one case low level mosaicism in blood was fortuitously detected because of cytogenetic fragile X screening and confirmed in a skin biopsy. The sixth case was of dynamic mosaicism of a non-mosaic deletion 18q with a chromosome 18 derived marker present in a proportion of cells. Chromosome mosaicisn may cause subtle and asymmetrical clinical features and can require repeated cytogenetic investigations. The diagnosis should be actively sought as it enables accurate genetic counselling to be given.